Legal acts operating in Poland concerning first aid - Misztal-Okońska, Patrycja Agnieszka; Goniewicz, Mariusz; Bednarz, Kamil (Journal of Education, Health and Sport, 2017)
Having knowledge and skills in first aid is extremely important as this has a huge impact on the health and life of the injured person during an emergency. In Poland, the issue of the obligation to provide first aid is governed by a number of legal acts, so that citizens can feel secure in the hope that they will be assisted by witnesses if necessary. The paper presents the legal acts in force in Poland that mention the obligation to provide first aid. Its aim, in addition to discussing the most important laws and regulations, is to emphasize the essential need to acquire and update skills in this area.